FinTech: A New Hedge for a Financial Re-intermediation. Strategy and Risk Perspectives - Omarini, Anna (Frontiers in Artificial Intelligence, 2020)
The emergence of new technologies and players, along with a favorable regulatory framework (PSD2 Directive), is changing the banking industry. FinTechs and TechFins have allowed the introduction of new services and changed the way customers interact to satisfy their financial needs. The FinTech landscape is constantly evolving in the market. Different business value propositions are entering the financial services industry, moving from increasing the user's experience to developing a time to market framework for banks to innovate products, processes, and channels, increasing the cost efficiency and looking for a “partnering on order” to lighten the regulatory burdens for banks. The many businesses of banks are changing their value chains, and banks' business models should do the same accordingly. Strategists could no longer take their value chains as a given; choices have to be made on what needs to be protected and maintained, what abandoned and the new on coming to make banks evolve and become more resilient in doing their job. Banking is shifting significantly from a pipeline, vertical paradigm, to open banking business models where open innovation, modularity, and ecosystem-based bank's business model may become the ongoing mainstream and paradigm to follow and develop. Opportunities and threats for banks are many and new ones to re-gaining their role in the market throughout a re-intermediation process.